Pengaruh Sosial Media Marketing dan Brand Image Terhadap Keputusan Pembelian - Stephen Wijaya, Novian; Anggraini, Dewi (Journal of Management and Economics Research, 2024)
This study aims to test whether there is an influence of social media marketing and brand image on purchasing decisions at Paulina Florist. The object of this research is customers at Paulina Florist. The basis for selecting this sample is the non-probabilty sampling method using accidental sampling techniques. The data applied in this study are primary data, data obtained from questionnaires distributed to 100 respondents. The analysis method used is the coefficient of determination with the help of spss 22, researchers also use Ghozali's theory (Chairunnisa et al., 2020). according to Ghozali, the coefficient of determination (R2) measures the model's ability to explain the variation in the independent variable on the dependent variable or it can also be said as the proportion of the influence of all independent variables on the dependent variable. The coefficient of determination can be measured by the R-Square value. Which means that the change in the output / dependent variable (Y) caused by the input / independent variable (X), is as large as the square of the correlation coefficient (r2). The coefficient of determination serves to determine the contribution or contribution given by one or more variables X to variable Y. Based on this test, the results obtained prove that social media marketing and brand image have an influence of 94% on purchasing decisions and the rest is influenced by other factors not examined.